Quality of life in patients after minimally invasive surgical correction of aortic valve diseases - Ivanyuk, A.; Rudenko, A.; Ponich, N.; Sagura, S.; Todurov, B. (Ukrainian Journal of Cardiovascular Surgery, 2017)
The assessment associated with the state of health of quality of life (QOL) is an important factor in determining the severity of the condition and strategy in surgical correction of aortic valve diseases. The aim of the study has been to estimate the quality of life of patients by the general medical questionnaire SF-36 in the postoperative period after the surgical correction of aortic valve diseases using the J-shape minimally invasive sternotomy in comparison with traditional approach. Materials and methods. In the State Institution «Institute Heart» of Ministre of Health from 2012 to 2016 analyzed the data of 102 patients with aortic valve diseases. Patients were sequentially inspected and selected for surgical correction of aortic valve diseases with different types of surgical approach. Results. In the comparative groups the statistically significant of the growth of the majority of scales varied: scales of bodily pain (59.9±24.4 versus 74.0±18.4, p=0.002) of the general health (39.7±17.5 versus 50.2±14.4, p=0.001), vitality (41.1±16.9 versus 52.2±16.6, p=0.001), social functioning (46.5±18.6 versus 60.7±20.1, p=0.001) and mental health (36.9±16.8 versus 46.6±13.8, p=0.005). Conclusions. Investigation has been shown that the minimally invasive approach improves the patient’s quality of life in the postoperative period and safe for the patient.